Dyadic Impact of Male Hypogonadism on Female Partners' Quality of Life, Emotional Well-Being, And Sexual Satisfaction in Couples Attending Fertility Clinics in Aba, Nigeria - Bertha Okwuchi Agu-Ikenna (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Background: Male hypogonadism is traditionally viewed as a male-specific endocrine disorder, yet its effects may extend significantly to female partners, particularly in fertility seeking couples. The dyadic impact—where one partner's biological condition affects the other's psychosocial and relational well-being—remains poorly characterised in sub Saharan Africa, including Nigeria. Understanding this dyadic impact is essential for developing couple-centred interventions that address the needs of both partners. Objective: To examine the association between male partner testosterone levels and female partners' quality of life (QoL), emotional well-being, and sexual satisfaction among couples attending fertility clinics in Aba, Abia State, Nigeria. Methods: A descriptive cross-sectional study was conducted from February to April 2024 at three fertility clinics in Aba: LifePoint Fertility Clinic, Royal Diamond Fertility Clinic, and M & M Fertility Clinic. Twenty female partners of male participants (from the same 20 couples) were recruited using purposive sampling. Inclusion criteria for female partners were: age 18–50 years, attendance at the fertility clinic with their male partner for at least three months, and written informed consent. Exclusion criteria included female partner being the sole identified cause of infertility or documented psychiatric comorbidity. Male partner serum total testosterone levels were extracted from clinic records (ECLIA method). Female partners completed the WHOQOL-BREF (26-item, four-domain QoL measure), a 5-item emotional well-being scale derived from the WHOQOL-BREF psychological domain, and a 5-item sexual satisfaction scale. All instruments demonstrated good reliability (Cronbach's α > 0.84 in pilot testing). Data were analysed using descriptive statistics, independent t-tests, and Pearson's correlation coefficient, with significance set at p < 0.05. Effect sizes (Cohen's d, r²) were calculated to quantify the magnitude of differences and associations. Results: Fifteen of the 20 male partners (75%) had low testosterone (<300 ng/dL), with a mean testosterone level of 248.6 ± 72.4 ng/dL. Female partners of men with low testosterone had significantly lower scores in all WHOQOL-BREF domains compared to those whose male partners had normal/borderline testosterone: physical (52.4 ± 8.6 vs. 65.2 ± 7.4, p = 0.003, Cohen's d = 1.52), psychological (40.8 ± 9.8 vs. 60.2 ± 8.4, p < 0.001, Cohen's d = 2.04), social relationships (36.6 ± 10.8 vs. 58.4 ± 8.6, p < 0.001, Cohen's d = 2.16), and environmental (46.8 ± 7.4 vs. 59.6 ± 8.2, p = 0.001, Cohen's d = 1.68). Mean emotional well being score was 9.6 ± 3.8 (out of 25) in the low testosterone group versus 19.4 ± 3.2 in the control group (p < 0.001, Cohen's d = 2.68). Sexual satisfaction was profoundly impaired(8.4 ± 3.2 vs. 18.6 ± 2.8, p < 0.001, Cohen's d = 3.36). Male testosterone level correlated strongly with female partner psychological QoL (r = 0.68, p < 0.001, r² = 0.46), emotional well-being (r = 0.68, p < 0.001, r² = 0.46), and sexual satisfaction (r = 0.72, p < 0.001, r² = 0.52). Sixty percent (9/15) of female partners of hypogonadal men reported poor or very poor emotional well-being compared to 0% in the comparison group. Seventy-three percent (11/15) of couples in the low testosterone group reported sexual dissatisfaction compared to 0% in the comparator group. Conclusion: Male hypogonadism exerts a significant, multi-dimensional negative dyadic effect on female partners' quality of life, emotional health, and sexual satisfaction. Female partners of hypogonadal men experience substantially poorer physical, psychological, and social functioning, high rates of emotional distress, and profound sexual dissatisfaction. The burden of male hormonal infertility is not confined to the affected man but extends profoundly to the female partner. The very large effect sizes (Cohen's d = 1.52–3.36) indicate clinically significant differences that warrant urgent attention. Recommendations: Fertility clinics should adopt couple-centred care models that include routine assessment of female partners' emotional and sexual health when male hypogonadism is diagnosed. Psychosexual counselling should be offered to both partners together, not individually. Nurses and other reproductive health professionals require training in dyadic assessment and intervention. Health policies should recognise infertility as a couple-level condition requiring couple-level services. Larger longitudinal and interventional studies are urgently needed to evaluate the effectiveness of couple-based interventions.